Omofobia nell’"Arialda" di Testori: Strategie di rappresentazione e dissimulazione - Pizzo, Antonio (Mimesis Journal, 2016)
This early work of Testori is read through the contemporary LGBT studies. Although, since the year of the frst Visconti’s mise en scène, was clear that the drama has been the frst Italian drama in which the homosexuality lays at the core of the plot, it has been less stressed the dramatic strategy used to expose such theme. The article describes how homophobia is a key figure to understand the author perspective on homosexuality and how the intimate struggle of the homosexual emerges through the dialectic among the non-homosexual characters. While Eros («the pervert») represent the social stigma, the relation between Arialda and Luigi stands for the inner anguish of the catholic homosexual.